ANALISIS PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PT. TELKOM TAHUN 2012-2020 (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Telekomunikasi Indonesia is developing very well in the economy aspect. This research was conducted to determine how the capital structure, financial performance, and the effect of capital structure on financial performance at PT. Telkom. The research method used is a quantitative method in the form of financial statements of PT. Telkom since 2012 to 2020. The total sample used in this study was 9, with a total of observational data is 36. The results of this study indicate that the capital structure and financial performance of PT. Telkom has developed well since 2012. And it was found that there is no significant effect of capital structure proxied by DAR and DER on financial performance proxied by ROA and ROE.